Performance Analysis of Highway Wind Turbine Enhanced with Wind Guide Vanes Using the Taguchi Method - Mazlan, Mohamad Zahid; Mohd Zawawi, Fazila; Tahzib, Teeab; Ismail, Kamarulafizam; Samion, Syahrullail (CFD Letters, 2021)
Considerable efforts have been made by researchers to study the interaction between moving vehicles and wind turbines. The Savonius vertical-axis wind turbine was chosen due to its effectiveness in low-wind speed conditions. Speeding vehicles produce a scattered and non-uniform wind flow with disturbances. Hence, to prevent a negative torque, a row of wind guide vane panels was arranged in front of the blades of a wind turbine. The wind guide vane had the shape of an NACA4412 aerofoil to reduce the loss of wind energy, and to further increase wind velocity. A number of CFD simulations were designed using the Taguchi method to determine the optimum conditions for the power coefficient of the wind turbine in terms of the effects of three factors, namely, the distance between the guide vanes (d), the angle of the guide vanes (?), and the speed of the moving car (VC). An orthogonal array of L9(33) was designed. In addition, to observe the effects of the wind velocity induced by the moving vehicle, the wind turbine was incorporated with one degree of freedom (1DOF). The results showed that the speed of the moving car played a major role in determining the power coefficient. The order of influence of each factor was ranked as VC > ? > d. The performance of the wind turbine was sensitive to the speed of the car and the angle of the guide vanes, whereas it was insensitive to the distance between the guide vanes. Furthermore, the analysis of the signal-to-noise (S/N) ratio suggested that the optimal combination of factors for a maximum power coefficient were d = 0.4m, ? = 30°, and VC =30m/s. The optimum setting increased the Cp to 26% compared to the Cp that was produced without the installation of the guide vanes.